Analysis of the Effect of Personal Characteristics and External Factors on Grit in Business Partners at PT Melia Sehat Sejahtera, East Java Branch - Davit Marcela Ananda; Gogor Arif Handiwibowo; Imam Baihaqi (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2023)
Purpose – This study aims to analyze and identify the influence of the role of Personal Characteristics and External Factors on Grit in business partners at PT Melia Sehat Sejahtera East Java branch. Methodology – This research is quantitative research with purposive sampling technique. Data collection was carried out onine via google form and offline through turnover and learning meetings with business partners of PT Melia Sehat Sejahtera branch of East Java as research respondents. A total of 112 data were successfully collected and processed using SmartPLS software using the PLS-SEM (Partial Least Square-Structural Equation Modeling) analysis method. Findings – The study's findings highlight the importance of identifying and nurturing grit in business partners to enhance their resilience and perseverance in facing challenges, thereby contributing to the company's long-term success and growth. Practical implications – This research is expected to have implications for the importance of supporting and strengthening personal characteristics and external factors that influence persistence (grit) in business partners at PT Melia Sehat Sejahtera, East Java Branch, to increase their resilience in facing business challenges and achieving sustainable success.